Manejo de azevém e de mecanismos sulcadores na implantação e desenvolvimento de soja em terras baixas - Coelho, Lucas Lopes (2017)
Soybean is an important alternative for the use of rotation system with irrigated rice. However, there’re some characteristics related to the soil, emphasizing the compaction and the difficulty of drainage, which are some of the obstacles to overcome to get a soybean production in a profitable way in these areas. In addition to this, there is also a need to review the management of the off-season. The use of cover crops in these areas appears not only as a necessity from the point of view of soil conservation, but also from income for the farmer. Nevertheless, plant managements should be provided for the purpose of not harming seeding and the development of the crop in succession. In this context, three studies were carried out in a systemized area of irrigated rice, with a typical soil of lowland areas (Albaqualf). The objectives of the studies are to: quantify the effect of periods of desiccation and haymaking of ryegrass on the initial establishment and development of soybean in succession (Chapter I); To determine the effect of seeding furrow opening mechanisms on the quality of seed distribution and initial establishment of plants (Chapter II); as well as on soil physical characteristics, plant growth and soybean yield in lowland areas with the presence of compacted layer (Chapter III). The experiments were conducted in the field in the lowland area of the Federal University of Santa Maria during the 2015/16 and 2016/17 growing season, and the experimental design was randomized block. In the experiment I, the treatments were composed by two ryegrass managements (hay and desiccation), five periods of desiccation and haymaking and one fallow (without ryegrass in the off-season). For experiments II and III, seeding furrow opening mechanisms were used, being: Shank at 0.23 m depth (HS at 0.23 m); Shank at 0.13 depth m (HS at 0.13 m); Double disk at 0.07 m depth and Raised-bed+Shank 0.12 m (Raised-bed + HS at 0,12 m). It was observed that early management (82, 73, 70 and 61 days before soybean seeding) provided better quality of the hay produced, however, a straw removal of the area resulted in reduction of soil potassium content. In addition, regardless of the time of haymaking and desiccation, the use of the cover plant increased the soil moisture at the time of sowing, thus reducing the initial plant stand and consequently soybean yield in relation to fallow (Chapter I). For the treatments with furrow opening mechanisms, it can be observed that the use of the shank in the area of fertilizer deposition, regardless of the depth and the use of moldboard, resulted in a great disparity in the deposition of seeds in depth. However, it didn’t affect the longitudinal distribution and initial establishment of plants (Chapter II). In the soil, HS at 0.23 m depth increased macroporosity and reduction of resistance to penetration to a depth of 0.2 m. This treatment cited, in addition to the Raised-bed + HS at 0.12 m depth allowed greater development of the root system, shoot growth and nodulation of the soybean plants, reflecting in an increase of the grain yield when compared to the systems of double disk and HS at 0.13 m depth (Chapter III).